Effectiveness of Learning through Play Plus (LTP Plus) Parenting Intervention on Behaviours of Young Children of Depressed Mothers: A Randomised Controlled Trial - Nusrat Husain; Rabia Sattar; Tayyeba Kiran; Mina Husain; Suleman Shakoor; Zamir Suhag; Zainab Zadeh; Siham Sikander; Nasim Chaudhry (MDPI AG, 2024)
Evidence has shown that parenting intervention programmes improve parental knowledge, attitudes, and practices, which helps in promoting child development. This study aims to examine the effectiveness of parenting intervention in improving child behaviours. This is a secondary analysis of data from a cluster-randomised controlled trial with depressed mothers aged 18-44 years with a child aged 0 to 36 months. This paper reports findings from the dataset of participants with a child aged between 24 and 36 months. Villages (n = 120) were randomised into either of two arms: learning through play plus (LTP Plus) or treatment as usual (TAU). LTP Plus is a 10-session, group parenting intervention integrated with cognitive behaviour therapy, delivered over 3 months. This secondary analysis reports findings on the Eyberg Child Behaviour Inventory (ECBI) and the Home Observation for Measurement of the Environment (HOME). Findings show a significant improvement in child behaviour (ECBI) scores (p < 0.011) and HOME scores (p < 0.001) in the intervention group compared to TAU at 3-month follow-up. In a low-resource setting, low-cost group parenting intervention delivered by community health workers has the potential to improve child behaviours and quality of the home environment. Parenting interventions aimed at improving child behavioural problems can have significant implications for the child, family, and broader societal outcomes. Addressing behavioural problems in early years, parenting interventions can potentially reduce long-term consequences and costs associated with untreated child behavioural issues.